IMPROVING READING COMPREHENSION BY USING DIRECTED READING ACTIVITY (DRA) - Fatih Al Fauzi (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2016)
Reading is one of the activities that can fulfill someone’s need, including student’s needs, particularly in getting the information needed. To know the condition of the students, the researcher used the pre test. The mean score of reading comprehension Pre Test was 37%. It show that the first condition is far from satisfied, hopefully the next steps will be better. Researcher use of Directed Reading Activity (DRA) to Improve Reading Comprehension. Type of research is classroom action research (CAR). The result of score analysis, in the first cycle shows that from 27 students there are only 59,3% of them who get score ≥ 75. This means that the rest of the students do not achieve the target score. Therefore, the action is continued to the second cycle. And in the second cycle, there are only 21.4% of them who get score ≤ 75, so the rest of them or 78.6 % of them get score ≥ 75. This means that more students achieve the target score. To sum up, the uses of Directed Reading Activity method was able improve the reading comprehension. Key words: Reading Comprehension, Directed Reading Activity, Improve.